PENERAPAN METODE KANO DALAM ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP PENEREPAN SISTEM INFORMASI AKADEMIK BERBASIS WEB - Hutabri, Ellbert (STKIP PGRI Sumatera Barat, 2015)
Academic information system is designed for data processing purposes academic. With the advanced information technology academic process can be managed into useful information in the Management college and decision making for top management in the college environment. Academic information system can be presented in the form of a website. Which contains features related to academic purposes. To see the effectiveness of the use of the website needs to be held evaluation. Evaluation can be done by measuring the level of user satisfaction to the features presented. The level of satisfaction can be measured with Kano method. Kano method is a method that aims to categorize the attributes of the products or services based on how well the product or service is able to satisfy its customers. This research is motivated by the use of web-based academic information system at the FKIP of University Muhammadiyah West Sumatra that does not satisfy the user. This study aimed to a) know how to Kano method in the application of the method to measure the level of student satisfaction, b) to determine student satisfaction toward web-based information systems academic using Kano, c) evaluating the lack of information systems in accordance with the needs of students, d) provide recommendations on UMSB management if there is dissatisfaction of students to academic web-based information systems. The results showed the level of satisfaction of students on the use of web-based information system as follows. First, there are two features in the website are in use is very satisfying for students. Secondly, six feature generates satisfied at the level of the student as user. Third, two features used students generate sufficient levels of satisfaction. Fourth, the features are less satisfied at the level of usage by students